Enhancing Students’ Secondary School Speaking Skill Through Storytelling - Roni Afrita; Rinda Rinda; Aida Fitrianah Zen (JETS: Journal of English Teaching Strategies, 2022)
The aims of the of this study is to find empirical evidence that storytelling technique can enhance students’ speaking ability at tenth grade of MA Bidayatul Hidayah. The total sample was 40 students. The method used of the research was quasi-experimental. The researcher chose the method because she wanted to know the effectiveness of storytelling technique in enhancing student’s speaking skill. The method used was quantitative. It means the method and instrument involved numerical measurement and then statistical quantification. the students’ speaking skill in experimental class that were given by the treatment through storytelling were improved more effectively than the control group. The conclusion storytelling is effective to be applied in teaching speaking skill. It can develop confidence, vocabulary, grammar, and comprehension.